Characterization of aerosol jet printed features at microwave frequencies - Teresa Cheng; Kelvin J. Nicholson (Advanced Manufacturing: Polymer & Composites Science)
Aerosol jet printing (AJP) is a promising direct-write technology that allows large stand-off distances between print head and target surface. Published works exploring AJP with conductive inks are rarely conducted at radio frequencies (RF) and so the utility of AJP in the antenna world has been limited. In this work, silver nanoink was deposited using a NanoJet™ AJP process, and the optimal printing parameters were determined by DC sheet resistance and RF conductivity measurements. A simple broadband planar inverted cone antenna (PICA) was fabricated where a minimum of 8 AJP layers was required to obtain a DC sheet resistance of 0.53 Ω/sq. and a bulk RF conductivity of [Formula: see text] S.m−1 over the bandwidth 2.0−26.0 GHz. This work has demonstrated that AJP can be utilized to fabricate bulk microwave components with acceptable electromagnetic performance and sets a solid foundation for the manufacturing of conformal antennas in the future.